Addressing sustainability in the requirements engineering process: From elicitation to functional decomposition - Saputri, Theresia Ratih Dewi; Lee, Seok Won (Journal of Software: Evolution and Process, 2020)
Due to the critical role of a software-intensive system in society, software engineers have a responsibility to add sustainability as a goal while developing a software system. However, there is a lack of practical guidelines providing a tangible decomposition of the sustainability aspect. Moreover, there are limited quantifiable methods to support sustainable design and analysis. Therefore, we propose a systematic approach that allows software practitioners to accommodate sustainability concerns that are aligned with other software quality attributes to enhance sustainable development. By using the combination of a goal-scenario-based approach and feature modeling, sustainability requirements are elicited along with their functional compositions. Our approach is a comprehensive reference model that decomposes sustainability requirements, enabling analysis, support, and assessment of sustainability risk analysis and guiding the designer to construct a feature model as a system functional decomposition. From the conducted theoretical evaluation and empirical study, our proposed approach can derive more significant sustainability-related requirements and key features by providing a practical guideline with the integration of well-known methods to address sustainability in requirements engineering. With the help of the provided approach, we can solve more conflicting goals in different sustainability dimensions.
Keywords: Functional decomposition; Goal modeling; requirements; Requirements engineering process; scenario; Software intensive systems; Software quality attributes; Sustainability dimensions; feature composition; goal model; requirements; risk analysis; scenario; sustainability